Literatur Review: Pengaruh Lingkungan Kerja, Pelatihan dan Motivasi Terhadap Kepuasan Kerja Karyawan CV. Kita Sukses Mandiri - Ajijah Jumani; Muhammad Richo Rianto (Studi Ilmu Manajemen dan Organisasi, 2023)
Purpose: This study aims to determine the effect of the work environment, training and motivation on employee job satisfaction. Methodology: In this method using a literature review using Google Scholar to be compiled and summarized in this study, in addition to the literature review it also uses references from various written data sources. Mendley and Google Scholar were widely used to write this article. Results: the results of this study can be said that motivation is not significant to employee job satisfaction that occurs in CV. We Succeed Independently. but in the system the variables of training and work environment variables are significant. meaning that motivation is an obstacle in this research but not too serious. Limitations: This research was only conducted on employees in the company. These variables include work environment, training and motivation to see the effect on employee job satisfaction. Contribution: The researcher hopes that this research can provide management with an overview of what conditions are currently happening in the company, and hope to provide insight into managing the company and creating a good working atmosphere so that it can have a positive influence on employee job satisfaction.